The indigenous movement and the economic trajectory of Ecuador - Kenneth P. Jameson (The University of Utah, Department of Economics, 2008)
On many measures, the indigenous movement in Ecuador has been the most successful in Latin America. This is particularly the case in political terms where they were key players until leaving the Gutiérrez cabinet. Their influence on the direction of economic policy has been minimal, however, and the rapid economic changes undertaken by the Correa administration since 2007 may marginalize them further. This paper examines Ecuador's checkered economic performance in the Washington Consensus period and the notable changes undertaken by Pres. Correa. These changes are then set in the context of the economic programs of the indigenous movement, specifically of CONAIE (Confederación de Nacionalidades Indígenas del Ecuador). This allows us to isolate several significant areas of overlap where the interests of the indigenous movement and of the Correa administration coincide and where collaboration on economic policy may be feasible.
Keywords: E65; O54; P40; Z13; 330; Ecuador; Indigenous movement; Pres. Correa; Policy Space